Effects of oxidizer and architecture on the thermochemical reactivity, laser ignition and combustion properties of nanothermite. (15th April 2022) - Wang, Weimin; Li, Hui; Zhang, Ming; Zhao, Fengqi; Xu, Siyu; Wang, Changjian; Qin, Zhao; An, Ting; Xu, Kangzhen
Highlights: A novel thermite nanocomposite (Al/CuFe2 O4 @NC) was assembled by an electrospray approach. The combustion performance of the thermite composites was adjusted by varying NC content. Laser ignition and combustion properties of the thermite composites were compared with common nanothermite. The Al/CuFe2 O4 @NC composites have short ignition delay time and excellent combustion performance. Abstract: Energetic materials have been widely employed in both military and aerospace fields. Nanothermite has superior energy properties and better combustion performance compared with conventional organic energetic materials. In this paper, a novel nitrocellulose coated aluminum/copper ferrite (Al/CuFe2 O4 @NC) thermite composite with moderate energy release was assembled via electrospray. The intimate contact and uniform distribution between the fuel (Al) and oxidizer (CuFe2 O4 ) are achieved in Al/CuFe2 O4 @NC microparticles. The thermochemical reactivity, laser ignition and combustion performance of Al/CuFe2 O4 @NC were investigated and compared with those of Al/CuO@NC, Al/Fe2 O3 @NC and physical mixture of Al and CuFe2 O4 (PM. Al + CuFe2 O4 ). The thermite reaction of Al/CuFe2 O4 @NC composite is dominated by the solid–solid reaction, which is similar to that of Al/CuO@NC and Al/Fe2 O3 @NC. Al/CuFe2 O4 @NC composite show a short ignition delay time of ∼ 4.0 ms and a moderate combustion process. The burning rates of Al/CuFe2 O4 @NC can be adjusted in the range of ∼ 0.39–1.77 m·s −1 by varying the content of NC in composite. In addition, the pressurization characteristics and condensed combustion products of thermite composites with different oxidizers were also investigated. The results indicate that the oxidizer and architecture have considerable effects on the thermochemical reactivity, laser ignition and combustion performance of thermite composite. The large heat release and superior ignition and combustion performance can be achieved by electrospray technology, which is an effective approach for enhancing interfacial contact.